Semi‐portable solar power to facilitate continuous operation of technology in the field. Issue 11 (9th August 2020) - Proppe, Darren S.; Pandit, Meelyn M.; Bridge, Eli S.; Jasperse, Philip; Holwerda, Charles
Abstract: The use of technology in field ecology is increasing rapidly and many applications require that equipment operates autonomously for weeks, months or even years. While reducing power requirements can extend the battery life of many field devices, research time frames are always limited without renewable power. However, commercially available units that provide autonomous solar power are either prohibitively expensive or too small to sustain continuous operation for many field devices. We describe a semi‐portable, field deployable solar unit that can provide sustainable power for a wide variety of field devices, including passive acoustic recorders, motion‐activated cameras, speakers and microcomputers. Depending on power needs, these units can be built in‐house for only a few hundred dollars (USD) with minimal access to tools or shop facilities. Further, we provide information on how to calculate power requirements and modify the system design to accommodate user needs. We have used these units effectively in the field for six research seasons, with continuous autonomous operation varying between 2 weeks and 8 months. Batteries and other parts are easily accessed and replaced if needed. Our example system can be modified to provide different output voltage (e.g. 12, 5 V), or to power audio speakers. We also describe a switch that can be placed within the unit to regulate power production to certain times of the day or week. Our aim is to facilitate the use of electronics in the field for ecologists who may lack funding, time or the expertise to design a system independently.